FANATISME PADA FANDOM BOY GROUP BTS (ARMY) MELALUI MEDIA SOSIAL TWITTER - Ratna Duhita Pramintari; Alfiana Indah Muslimah; Kartika Syafriani; Kinanthi Mutiara Shafa; Yulianti Indah Permatasari (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2022)
The Korean culture that entered Indonesia brought several influences, one of which was the entry of the genre of pop music, commonly called K-pop. The number of people who are interested in this genre of music has various impacts, namely the number of people, especially teenagers, who show conformity and fanaticism. Community fanaticism is shown through several social media platforms, one of which is Twitter. The purpose of this study was to determine the behavior of fanaticism in the Fandom Army in carrying out their activities on Twitter social media. The sampling strategy used is homogeneous with a purposeful sampling technique, which is a technique where researchers choose subjects and places with the aim of studying or understanding central phenomena. The criteria used are BTS Boy Group fans who use Twitter, know the background and current information about their idols, and have a high sense of love for their idols. In research that uses this qualitative method, 2 informants are used to help provide data on the main subject. Semi-structured interview techniques were used to collect data, and thematic coding analysis was used to analyze observations. The results of this study indicate that the fanatic behavior of Army fanatics on Twitter indicates a tendency toward positive fanaticism.